2014
DOI: 10.24297/jac.v10i6.6668
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Chemical Treatments on the Tensile Behaviour of Abaca Fiber Reinforced Polypropylene Composites

Abstract: Abaca fibers were subjected to different chemical treatments like alkali treatment, permanganate treatment, acrylation & benzene diazonium chloride treatment and these chemically treated fibers were used as reinforcements in the preparation of polypropylene composites by hot compression moulding method. Various composites were fabricated with different fiber loadings of 20%, 30%, 40%, 50%, 60%, and 70%. Abaca composites with 40% fiber loadings were found to have optimum properties when tensile tests were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…[16] in their investigation of rice husks in relation to their alkali-treated forms reported that alkali treated rice husks absorbed water higher than their untreated counterpart. The treatment of the fillers with outstanding mechanical properties has been reported to be more favourable with diazonium salt treatments than mercerization and other treatment methods [9,14,17,18]. Hence, the need to subject rice husk to various pH levels of this treatment to ascertain the appropriate concentration that will yield better properties for developed biocomposites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] in their investigation of rice husks in relation to their alkali-treated forms reported that alkali treated rice husks absorbed water higher than their untreated counterpart. The treatment of the fillers with outstanding mechanical properties has been reported to be more favourable with diazonium salt treatments than mercerization and other treatment methods [9,14,17,18]. Hence, the need to subject rice husk to various pH levels of this treatment to ascertain the appropriate concentration that will yield better properties for developed biocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, comparing benzene diazonium chloride with mercerisation, acrylation and permanganate treatments on abaca fibres, researchers [17,18] reported that the benzene diazonium chloride treated abaca reinforced polypropylene composites showed excellent interfacial bonding characteristics and mechanical properties resulting in the best tensile strength with optimum properties noticed at the 40% fibre loading. [21] similarly utilized diazonium salt in the treatment of palm fibres which was used in reinforcing polypropylene and established that benzene diazonium salt dissolved the hydroxyl groups in the acid media with a pH of 3, the alkaline media with a pH of 10.5 and the neutral media with a pH of 7.…”
Section: Introductionmentioning
confidence: 99%
“…However, chemical treatments of the fiber surface can mitigate this. Researchers have tried various types of chemical treatment such as alkaline, silane, acetylation, acrylation, maleated coupling agent, and so on (Fiore et al, 2015;Liu et al, 2019;Sood & Dwivedi, 2018;Chung et al, 2018;Punyamurthy et al, 2014;Anbupalani et al, 2020). This surface treatment process of fiber substantially improves the attachment between the polymer and fiber, which brings out better material characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical treatment may be used to improve hydrophilic in nature of natural fibre, interfacial bonding between matrix and fibre, surface roughness, wettability and decreased moisture absorption, thermal and electrical properties (Beckermann and Pickering, 2008;Noranizan and Ahmad, 2012;Raj et al, 2011). Many researchers have applied mercerization and acetic anhydride treatment with remarkable improvement in the mechanical properties of both treated fibres and/or composites at optimum conditions (Hossain et al, 2014;Punyamurthy et al, 2014;Singha and Thakur, 2014;Tlijania et al, 2014;Noorunnisa et al, 2011;Zhong et al, 2010). Higher concentration of alkali solution may also lead to excess delignification of fibre which weakens and damages the fibre (Li et al, 2007).…”
Section: Introductionmentioning
confidence: 99%